A template-based approach for parallel hexahedral two-refinement. (April 2017) - Owen, Steven J.; Shih, Ryan M.; Ernst, Corey D.
Abstract: We provide a template-based approach for generating locally refined all-hex meshes. We focus specifically on refinement of initially structured grids utilizing a 2-refinement approach where uniformly refined hexes are subdivided into eight child elements. The refinement algorithm consists of identifying marked nodes that are used as the basis for a set of four simple refinement templates. The target application for 2-refinement is a parallel grid-based all-hex meshing tool for high performance computing in a distributed environment. The result is a parallel consistent locally refined mesh requiring minimal communication and where minimum mesh quality is greater than scaled Jacobian 0.3 prior to smoothing. Highlights: All-hex conformal refinement of Cartesian grids. New template-based two-refinement algorithm. Distributed parallel algorithms for high performance computing. Parallel consistent with minimum quality guarantee.